The biology of gobies - Patzner, Robert A.; Tassell, James L. Van; Kovacic, Marcelo; Kapoor, B.G (Science Publishers, 2011)
"Among all vertebrates, gobies are second in diversity only to the teleost family Cyprinidae. The Gobiidae consists of more than 200 genera and nearly 2,000 species and make up the largest family of marine fishes. Gobies account for as much as 50% of the energy flow in coral reef communities. Their small size, ability to adapt to numerous ecological niches and to be bred in aquaria has led to numerous studies both in the field and laboratory. Gobies are found from above the high tide line to depths of over 1,100 m. Some species are found only within caves, others deep inside sponges, and some others climb waterfalls to return to their native streams. They vary reproductively from gonochoric to hermaphrodite, monogamy to polygyny and promiscuity, some have short life spans and reproduce only once while others have longer life spans reproducing one or more times per year. The Biology of Gobies written by over 30 experts from 15 countries summarizes what is known about the systematics, ecology, zoogeography, and general biology of the Gobiiformes. This foundation will provide the basic information necessary for future studies"--Provided by publisher.